(untitled) (Belgium, 1991)
Much new information is presented in this new edition, including details of the impact of genetically modified food products and a new chapter on the sustainability of aquaculture, which covers the definitions of sustainability and responsible aquaculture, environmental, economic, social and ethical aspects of sustainability and the concept of ecotechnology in fish farming.
Keywords: Aquaculture,Nuôi trồng thủy sản,Fisheries,Nghề cá; Environmental aspects,Khía cạnh môi trường